ووجدک ضالا فھدٰی"کی تعبیرات میں اختلاف وتطابق: منتخب اردو تراجمِ قرآن کا مطالعہ": Difference and Consensus in the Interpretations of "ووجدک ضالا فھدٰی": A Study of Selected Urdu Translation of the Quran (Al-Qamar, 2019)
Qur’ānic exegesis approaches differently in interpreting the verses related to scholastic issues like attributes of Allah, honor of the prophets, etc. The reasons for these differences could be the difference of interpretation, implementation of Qur’ānic sciences, understanding of the environment of a revelation and inclination of translators towards their specific schools of thought. In the Indian subcontinent, a notable difference, in the various translations, can be observed from referred perspective. This article deals with the difference and consensus regarding the interpretations of the Qur’ānic words: "ووجدک ضالا فھدٰی"in the light of selected Urdu translations of the Quran
Keywords: Qur’ānic exegesis; ووجدک ضالا فھدٰی; Urdu translations of the Quran